A numerical model for duricrust formation by water table fluctuations - C. Fenske; C. Fenske; J. Braun; J. Braun; F. Guillocheau; C. Robin (Earth Surface Dynamics)
Duricrusts are hard mineral layers forming in climatically contrasted environments. They form in tropical to arid environments and can be currently observed all around the world in areas such as Europe, Africa, South America, India, and Australia. In most cases, they cap hills and appear to protect softer layers beneath. Two main hypotheses have been proposed for the formation of duricrusts; i.e. the hydrological or transported model, where the enrichment in the hardening element (iron for ferricretes, silica for silcretes, or calcium carbonates for calcretes) is the product of leaching and precipitation through fluctuations in the water table during contrasted seasonal cycles, and the laterization or in situ model, where the formation of duricrusts is the final compacting stage of laterization.